Pengaruh Penggunaan Sumber Belajar Terhadap Hasil Belajar Fisika Kelas XI di SMA Muhammadiyah 2 Palembang - Devi Ardiantini; Tanti Febrianti; Hamdi Akhsan; Kistiono (JIPFRI (Jurnal Inovasi Pendidikan Fisika dan Riset Ilmiah), 2025)
This study aims to analyze the influence of learning resource utilization on the physics learning outcomes of Grade XI students at SMA Muhammadiyah 2 Palembang. The learning resources examined include textbooks, instructional videos, and online materials. The research instrument consists of 10 validated survey items designed to represent key indicators of learning resource use, such as frequency of utilization, diversity of sources, and relevance of materials. The survey was administered to 73 randomly selected respondents via Google Forms. Data were analyzed using simple linear regression. The results show a significance value of 0.000013 (< 0.05) and an F-value of 22.010, which exceeds the F-table value of 3.94, indicating a significant influence of learning resource utilization on students’ physics learning outcomes. Thus, the more optimally learning resources are utilized, the higher the students’ achievement in physics.